The Development of Learning Materials Students' Book Based on Contextual that Integrated with Technopreneurship in Biotechnology Subject at XII Grade Senior High School - Linda Kusumawati; Suratno Suratno; Erlia Narulita (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Biotechnology has growth fast in the last 20 years. Biotechnology produces many products biotechnology, so in some developed countries serve as the centre of bioeconomic activities. The rapid development of science and technology makes biotechnology must be mastered by academics including students. Efforts to improve the mastery of biotechnology can be pursued by using the contextual and integrated technopreneurship lesson. This research is a development research using 4D model (four D model), which consists of four stages, namely Define, Design, Develop, and Disseminate. However, the implementation of this research is limited to Define, Design, and Develop stage. The book validation value of the students developed based on experts and users is 92.23% and 92.48% with very reasonable criteria. Value of the book of students based on test book readability of student equal to 88,63% with criteria very good and result of student response after using book equal to 93,71% with criterion very good so that book can be said practical and can be used for field study activity.